The Influence of Interactive Teaching Materials Based on Tpack To Ability Literacy and Learning Outcomes Student Class XI IPA 1 SMA Negeri 4 Sigi on the Drama Material The End of the Tyrant - Kadir, Wulandari; Latief, Juraid Abd; Idrus (Kirana Publisher (KNPub), 2025)
This study aims to analyze the influence of the use of interactive teaching materials based on TPACK ( Technological Pedagogical Content Knowledge ) on students' literacy skills and learning outcomes. class XI IPA 1 SMA Negeri 4 Sigi on the material Drama Akhir Sang Tirani . The background of this study is based on the need for learning innovations that are able to integrate technology, pedagogy, and content effectively in improving the quality of learning in the digital era. The research method used is the method quantitative through quasi-experimental with pretest-posttest control group design . The research subjects consisted of two classes, namely the experimental class using TPACK- based interactive teaching materials and the control class using conventional teaching materials. The instruments used included a questionnaire. ability literacy and learning outcome test questions students. The results of the data analysis show that there are significant influence between the experimental class and the control class both in literacy skills and learning outcomes with distribution of questionnaire data in posttest class experiment 33 % in the very high category and 67% in the low category high . While in the posttest class control by 57% category high and 43% category medium . So that it is said results obtained​ class experiment more Good compared to class control . While the data on the results Study show student with average value on posttest class experiment more Good that is by 77 compared to class control with value 59. So the self in the experimental class experienced a higher increase compared to the control class. This finding shows that the integration of the TPACK model in the use of interactive teaching materials has a positive impact on improving literacy and student learning outcomes. Therefore, it is recommended for educators to adopt the TPACK approach in designing teaching materials in order to create more effective and relevant learning to the needs of the times.